Sustainable Stabilization of Peat Soil Using Hydrated and Expanded Perlite - Md Yusof, Zeety; Let, Mohamad Afiq; Maha Agung, Putera Agung; Leow, Chee Sin (International Journal of Sustainable Construction Engineering and Technology, 2025)
Peat soil, due to its weak engineering properties, poses significant challenges in geotechnical applications. This review critically examines the potential of using sustainable stabilizers, specifically hydrated lime (HL) and expanded perlite (EP), for peat soil stabilization. Studies published in 2020 - 2025, along with selected earlier works, were analyzed to evaluate the effectiveness and performance in enhancing peat soil properties, particularly through Unconfined Compressive Strength (UCS) tests. Impressive UCS improvements were reported, such as a 13,553.2% increase with quarry dust (QD) and ordinary Portland cement (OPC). However, not all studies included microstructural analysis; those that did utilized Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) to observe bond formation and structural changes in stabilized peat. The review concludes that HL and EP show promise as sustainable alternatives for stabilizing peat, though challenges remain regarding their long-term performance and the potential benefits of combining both stabilizers. Further research is needed to optimize their dosage, durability, and environmental impact under field conditions.